Optimizing the organization of infill walls in order to improve the earthquake response - Guney, D.; Kuru, A. O.; Vatan, M. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2010)
The contribution of infill walls in the earthquake resistant building design generally is not taken into account. Although the infill walls are considered as non-structural elements and are ignored in the analysis these elements tend to interact with the frame in case of lateral load effect. The aim of this paper is to indicate the contribution of infill walls in the earthquake resistant building design. First bare structure is analyzed the four different types of configuration of infill walls are analyzed as numerical models. Consequently, according to the analysis results of structural configurations, the behavior of the structure subjected to the earthquake loading is evaluated.
Keywords: MASONRY INFILLS; Engineering